2011
DOI: 10.1177/147323001103900534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Cuff Pressure Regulator in General Anaesthesia with Laryngeal Mask Airway

Abstract: Postoperative pharyngolaryngeal complications (PPLC) occur during anaesthesia due to increased cuff pressure following the insertion of laryngeal mask airways. The use of a pressure regulator to prevent PPLC was evaluated in a prospective, randomized study. Sixty patients scheduled to receive general anaesthesia were randomly assigned to two equal groups of 30, either with or without the regulator. The 'just seal' cuff pressure (JSCP), cuff pressure at 5-min intervals during anaesthesia, incidence of pharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…The LMA was inserted after the patient lost consciousness and eyelash reflex. The LMA size was chosen according to the gender and weight of the patient: size 3 (>50 kg) or size 4 (≤50 kg) for women; size 4 (<70 kg) or size 5 (≥70 kg) for men (11). LMA cuff pressure was adjusted to less than 44 mmHg (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LMA was inserted after the patient lost consciousness and eyelash reflex. The LMA size was chosen according to the gender and weight of the patient: size 3 (>50 kg) or size 4 (≤50 kg) for women; size 4 (<70 kg) or size 5 (≥70 kg) for men (11). LMA cuff pressure was adjusted to less than 44 mmHg (12).…”
Section: Methodsmentioning
confidence: 99%
“…LMA-induced pharyngolaryngeal complications (POST, hoarseness, dysphagia) are related to the insertion technique, number of insertion attempts, LMA size, duration of anaesthesia and surgical position (11,(14)(15)(16). Studies have shown that the use of lubricants to facilitate insertion and cuff pressure control does not reduce the incidence of sore throat (2).…”
Section: Turk J Anaesth Reanim 2014; 42: 123-7mentioning
confidence: 99%
“…Smaller tube size [5][6][7] Use of i-gel [50,[63][64][65] SAD rather than tracheal tube [121,122] Video laryngoscopy [9,10] 90°rotational insertion technique, use of introducing stylet for ProSeal LMA laryngeal mask [81][82][83][84][85] Oral rather than nasotracheal intubation [124] Limiting cuff pressure [32][33][34] Cuff pressure limitation ≤ 60 cmH 2 O [88][89][90][91][92][93]96] Cuffed rather than uncuffed tubes [125] Intravenous, topical or inhaled steroids [22][23][24][25] Topical steroids, NSAIDs, tramadol [98,101,102] Limiting tracheal tube cuff pressure [126] Topical NSAIDs [27][28][29]31] Propofol induction and maintenance [106,107] SAD cuff pressure limitation ≤ 60 cmH 2 O [130][131][132][133] Liquorice, magnesium and ketami...…”
Section: Tracheal Intubation Sads Childrenmentioning
confidence: 99%
“…These may result from both increased mucosal pressure and the failure to conform to the contours of the larynx, pharynx and oesophagus. Published adverse effects include recurrent laryngeal nerve palsy , dysphonia, dysphagia and venous congestion , with its attendant risks of airway oedema and surgical bleeding.…”
Section: Myth 5: the Worst That Can Happen Is A Sore Throatmentioning
confidence: 99%